Pressure release superleak sound modes in He II - Heckerman, David; Rosenbaum, Ralph; Putterman, Seth; Williams, Gary A. (Journal of Low Temperature Physics, 1980)
The sound modes of He II in a waveguide partially packed with superleak are investigated for the case of a free surface within the waveguide. In the limit of zero vapor density, two propagating modes are found: one a gravity wave whose velocity depends on the superfluid fraction, and the other a temperature wave which is analogous to adiabatic U-tube osculations. With finite vapor the U-tube mode in pure 4He mixes strongly with the vapor sound; however, in 3He-4He mixtures it is uncoupled from the vapor and is observable. Experimental results are in qualitative agreement with the theory.